Pengaruh Pemberian Pisang Ambon Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi Di Pstw Sicincin - Larasuci Arini; Setiadi Syarli (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
This study discusses the relationship between ambon banana consumption and blood pressure reduction in the elderly with hypertension. Hypertension is a serious health problem, especially in the elderly, and has a significant impact on organs such as the heart, brain, and kidneys. In several studies, it was found that regular consumption of pisang ambon can reduce blood pressure in elderly people with hypertension. Ambon bananas contain potassium, which can help maintain blood pressure balance. The results of various research suggest that non-pharmacological therapies, such as the consumption of pisang ambon, can be an effective option in lowering blood pressure in the elderly with hypertension. Intervention through consumption of pisang ambon in complementary therapy showed positive results in lowering blood pressure, but further research can provide a deeper understanding of the effectiveness of this therapy in the elderly population with hypertension problems.